Entangled metallic porous material–silicone rubber interpenetrating phase composites with simultaneous high specific stiffness and energy consumption - Zheng, Xiaoyuan (2024)
High stiffness and superior energy consumption have consistently been primary research focuses in the field of damping materials. Hence, this work presented an innovative interpenetrating phase composite (IPC) crafted from wound elastic entangled metallic porous material and silicone rubber. The proposed composite effectively integrates the unique properties of the original materials, showcasing a seamless blend. Dynamic experimental tests were conducted to analyze the dynamic compression mechanical behavior of the composites, revealing that the composites exhibit excellent energy consumption capabilities and elevated stiffness characteristics. The improvement in both stiffness and damping characteristics is attributed to the addition of silicone rubber, which solidifies the structure of the composites. The introduction of interfacial friction results from maintaining compression, sliding, and other frictional interactions among the original spiral coils. Notably, the composites also display exceptional fatigue resistance. Overall, this work demonstrates the potential to concurrently achieve enhanced stiffness and superior energy consumption through the use of entangled metallic porous material and silicone rubber.